The Khorana score for prediction of venous thromboembolism in cancer patients: An individual patient data meta‐analysis. (8th July 2020) - van Es, Nick; Ventresca, Matthew; Di Nisio, Marcello; Zhou, Qi; Noble, Simon; Crowther, Mark; Briel, Matthias; Garcia, David; Lyman, Gary H.; Macbeth, Fergus; Griffiths, Gareth; Iorio, Alfonso; et al.
Abstract: Background: Oncology guidelines suggest using the Khorana score to select ambulatory cancer patients receiving chemotherapy for primary venous thromboembolism (VTE) prevention, but its performance in different cancers remains uncertain. Objective: To examine the performance of the Khorana score in assessing 6‐month VTE risk, and the efficacy and safety of low‐molecular‐weight heparin (LMWH) among high‐risk Khorana score patients. Methods: This individual patient data meta‐analysis evaluated (ultra)‐LMWH in patients with solid cancer using data from seven randomized controlled trials. Results: A total of 3293 patients from the control groups with an available Khorana score had lung (n = 1913; 58%), colorectal (n = 452; 14%), pancreatic (n = 264; 8%), gastric (n = 201; 6%), ovarian (n = 184; 56%), breast (n = 164; 5%), brain (n = 84; 3%), or bladder cancer (n = 31; 1%). The 6‐month VTE incidence was 9.8% among high‐risk Khorana score patients and 6.4% among low‐to‐intermediate‐risk patients (odds ratio [OR], 1.6; 95% confidence interval [CI], 1.1‐2.2). The dichotomous Khorana score performed differently in lung cancer patients (OR 1.1; 95% CI, 0.72‐1.7) than in the group with other cancer types (OR 3.2; 95% CI, 1.8‐5.6; Pinteraction  = .002). Among high‐risk patients, LMWH decreased the risk of VTE by 64% compared with controls (OR 0.36; 95% CI, 0.22‐0.58), without increasing the risk of major bleeding (OR 1.1; 95% CI, 0.59‐2.1). Conclusion: The Khorana score was unable to stratify patients with lung cancer based on their VTE risk. Among those with other cancer types, a high‐risk score was associated with a three‐fold increased risk of VTE compared with a low‐to‐intermediate risk score. Thromboprophylaxis was effective and safe in patients with a high‐risk Khorana score.